Bubble - Poh, Ya Ching (2014)
Bubble is a short 3d animated film that explores the relationship between two characters - a cat and a girl. The film is set in a small Southeast Asian village in the 1980s. The film opens little windows into the life between the characters, from the moment when the cat arrives till its departure. The narrative of the story is more spontaneous and less structured to make room for a more emotive interpretation. Bubble is produced by Korny Poh, Yulin Quek, and Zig Lam.